Conceptualizing Motherhood Through Metaphors of Grief and Hope - Azra Latifah Setiady; Sarah Fadilah; Bilbina Azzahara Usman; Dhuha Hadiyansyah (Prosiding Seminar Nasional Pemberdayaan Masyarakat (SENDAMAS), 2025)
Language is not only a tool for communication, but also a cognitive device  that enables individuals to understand and interpret their life experiences. By addressing the issue of how language reflects emotional experiences related to loss and recovery within parenting communities, showing how metaphorical expressions reflect Western perceptions of motherhood and emotional resilience. This research aims to explore how conceptual metaphors, namely baby blues, sunshine baby, rainbow baby, angel baby, golden baby, and sunrise baby reflect emotional experiences, coping mechanisms, and meaning-making processes among parents who have experienced childbirth or infant loss. The study involved qualitative descriptive analysis with purposive sampling of online narratives shared by parents, following stages of data collection, metaphor identification, and conceptual mapping The results reveal that light, color, and nature metaphors are dominant, showing how linguistic expressions transform grief into shared narratives of hope and healing, in accordance with the study’s objective to explore language as a cognitive and emotional tool.Keywords – Baby, Experience, Metaphore, Motherhood, Parenting